2022
DOI: 10.7196/samj.2022.v112i8.16480
|View full text |Cite
|
Sign up to set email alerts
|

The tragedy of smoking, alcohol, and multiple substance use during pregnancy

Abstract: Background. Antenatal substance use is a significant public health concern in South Africa (SA). Information on smoking, drinking and drug use during pregnancy was collected prospectively for the Safe Passage Study of the PASS (Prenatal Alcohol in Sudden infant death syndrome and Stillbirth) Network.Objectives. Data from 4 926 pregnant women in a community near Tygerberg Academic Hospital, Cape Town, were examined to determine whether associations between different substance use groups and postnatal infant out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Unexpectedly, we found an increase in birth weight after PAE during third trimester, which was also found in preterm newborns in another analysis in the same population [ 41 ]. Contrasting, another study in a bigger Safe Passage sub-cohort found smaller birth weight Z -scores in alcohol exposed fetuses, although Brink et al investigated PAE as categorical variable, causing loss of information and possible misinterpretation of actual effect sizes [ 24 ]. Moreover, in our study, most women consumed alcohol during periconception period and first trimester, after which the amount of self-reported alcohol consumption decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, we found an increase in birth weight after PAE during third trimester, which was also found in preterm newborns in another analysis in the same population [ 41 ]. Contrasting, another study in a bigger Safe Passage sub-cohort found smaller birth weight Z -scores in alcohol exposed fetuses, although Brink et al investigated PAE as categorical variable, causing loss of information and possible misinterpretation of actual effect sizes [ 24 ]. Moreover, in our study, most women consumed alcohol during periconception period and first trimester, after which the amount of self-reported alcohol consumption decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed study protocol is described elsewhere [ 23 ]. Previous studies in the South African arm of the cohort showed a reduction in birth weight Z -scores in neonates prenatally exposed to alcohol [ 24 , 25 ]. However, PAE as variable was categorized, causing difficulties in interpretation of PAE-effects.…”
Section: Methodsmentioning
confidence: 99%